2014
DOI: 10.4161/auto.36183
|View full text |Cite
|
Sign up to set email alerts
|

Acidocalcisome is required for autophagy inTrypanosoma brucei

Abstract: target of rapamycin complex 1; polyP, polyphosphate; PPi, pyrophosphate; PtdIns3K, phosphatidylinositol 3-kinase; PtdIns3P, phosphatidylinositol 3-phosphate; RNAi, RNA interference; T. brucei, Trypanosoma brucei; Tbb3, the b3 subunit of adaptor protein-3 complex in Trypanosoma brucei; Tbd, the d subunit of adaptor protein-3 complex in Trypanosoma brucei; TbVMA1, the subunit A of V-H C -ATPase in Trypanosoma brucei; TbVP1, vacuolar pyrophosphatase in Trypanosoma brucei; TbVPH1, the a subunit of V-H C -ATPase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 56 publications
2
45
0
Order By: Relevance
“…Another important function demonstrated recently was the involvement of acidocalcisomes in autophagy in T. brucei [71]. Treatment of procyclic stages with bafilomycin A 1 (a V-H + -ATPase inhibitor), monensin (a Na + /H + ionophore), or the combination of NH 4 Cl and ionomycin (alkalinizing agents) inhibited starvation-induced autophagosome formation, suggesting the need for functional acidic organelles for autophagy to occur.…”
Section: Novel Functionsmentioning
confidence: 99%
“…Another important function demonstrated recently was the involvement of acidocalcisomes in autophagy in T. brucei [71]. Treatment of procyclic stages with bafilomycin A 1 (a V-H + -ATPase inhibitor), monensin (a Na + /H + ionophore), or the combination of NH 4 Cl and ionomycin (alkalinizing agents) inhibited starvation-induced autophagosome formation, suggesting the need for functional acidic organelles for autophagy to occur.…”
Section: Novel Functionsmentioning
confidence: 99%
“…As indicated above the presence of mechanisms for Ca 2+ uptake (Ca 2+ -ATPase) and release (IP 3 R) suggest a role in Ca 2+ signaling [6]. A role in autophagy in T. brucei was recently revealed [43]. Downregulation of components of the AP-3 complex, involved in acidocalcisome biogenesis, inhibits starvation-induced autophagosome formation [43].…”
Section: Introductionmentioning
confidence: 99%
“…A role in autophagy in T. brucei was recently revealed [43]. Downregulation of components of the AP-3 complex, involved in acidocalcisome biogenesis, inhibits starvation-induced autophagosome formation [43]. In T. cruzi, several studies reported the role of acidocalcisomes in osmoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…The core autophagy events, from double-membraned autophagosome formation to the final degradation in lysosomes are conserved [8], and autophagy-related functions of several ATG homologs or protein complex including ATG3, ATG5, ATG7, ATG24 and PI3K have also been confirmed [8,[13][14]. Interestingly, the acidocalcisomes, a lysosome-related organelle found in trypanosomes and some other protozoan parasites are found to be required for autophagy induction [15]. In higher eukaryotes, the lysosomes are not only involved in the last degradation step of autophagy, but also involved in the induction step through mTOR signaling.…”
Section: Autophagy In T Bruceimentioning
confidence: 95%